Picturing Canada : a history of Canadian children's illustrated books and publishing - Edwards, Gail (Studies in book and print culture., 2010)
An interdisciplinary history, Picturing Canada provides a critical understanding of the changing geographical, historical, and cultural aspects of Canadian identity, as seen through the lens of children's publishing over two centuries.